2014
DOI: 10.21547/jss.257178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Teachers' Opinions About Effective Classroom Management Practices

Abstract: ÖzetBu araştırmanın amacı; etkili bir sınıf yönetim süreci oluşturulmasında öğretmen davranışlarının ilkokul ve ortaokulda görev yapan öğretmenlerin görüşlerine dayanarak değerlendirmektir. Nitel bir çalışma olup durum çalışması deseni kullanılmıştır. Veri toplamak amacıyla ilgili literatür taranmış ve araştırmada kullanılmak üzere 9 adet açık uçlu soru hazırlanmıştır. Bu sorular, maximum çeşitlilik örnekleme yöntemine dayanılarak belirlenen 18 öğretmene yöneltilmiştir. Veriler görüşme formu aracılığı ile topl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…teachers and children, in the process of determining the rules can strengthen the child's feeling of belonging to the class, can help children adopt and internalize the rules, and thus can increase the validity of the class rules. By setting class rules together, children feel valued, they become willing to follow rules, their desire to follow rules increases, the development of democracy perception is supported, and rules are more easily internalized (Burden, 2003;Doğan, Uğurlu & Karakaş, 2014;Durmuşoğlu Saltalı & Arslan, 2013;Karabay & Asi, 2015;Kerr & Nelson 2010). Positive approaches that allow children to participate in classroom management and activities by expressing their opinions enable children to be an active participant in the center of the educational process (Koran & Avcı, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…teachers and children, in the process of determining the rules can strengthen the child's feeling of belonging to the class, can help children adopt and internalize the rules, and thus can increase the validity of the class rules. By setting class rules together, children feel valued, they become willing to follow rules, their desire to follow rules increases, the development of democracy perception is supported, and rules are more easily internalized (Burden, 2003;Doğan, Uğurlu & Karakaş, 2014;Durmuşoğlu Saltalı & Arslan, 2013;Karabay & Asi, 2015;Kerr & Nelson 2010). Positive approaches that allow children to participate in classroom management and activities by expressing their opinions enable children to be an active participant in the center of the educational process (Koran & Avcı, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Sınıf kurallarının beraber belirlenmesi, çocukların kendilerini değerli hissetmelerini, kurallara uymaya gönüllülük göstermelerini sağlayabilmekte, çocukların kurallara uyma isteklerini arttırabilmekte, demokrasi algılarının gelişimini destekleyebilmekte ve kuralları içselleştirmelerine yardımcı olabilmektedir. (Burden, 2003;Doğan, Uğurlu & Karakaş, 2014;Durmuşoğlu Saltalı & Arslan, 2013;Karabay & Asi, 2015;Kerr & Nelson 2010). Sınıf yönetimi ve etkinliklerine çocukların da fikirlerini belirterek katılmalarına izin veren olumlu yaklaşımlar sayesinde çocuklar eğitim sürecinin merkezinde aktif bir katılımcı olarak yer alırlar (Koran & Avcı, 2017).…”
Section: Tartışma Ve Sonuçunclassified
“…In a qualitative study conducted on 18 teachers by [14] showed that teachers are aware of the importance of time management.…”
Section: Time Managementmentioning
confidence: 99%
“…A study done by [14] on 18 teachers regarding efficient classroom management shows that in order to make students achieve self-confidence there should be warm interactions in class and that teacher should be exemplary to students.…”
Section: Relationships In Classmentioning
confidence: 99%
See 1 more Smart Citation